(untitled) (Il Risorgimento. Rivista di storia moderna e contemporanea, 2024)
This article investigates the security dynamics of the Papal States adopted in the Ionian Islands during the 1850s. Through the analysis of confidential correspondence between the General Consul, Savini, and the Secretary of State, Antonelli, the study reveals the evolution of the security practices of the Holy See after the turn of 1848-49. The analytical basis of this study derives from the professional background of the newly appointed consul Savini, captain of the Papal Dragoons. In the context of a strong emergency, the Holy See had decided to send a military figure as a diplomatic agent to bring its administration into line with the emerging field of trans-state police expertise. The changes implemented by Savini describe this intention from the beginning of his tenure in the agency. These brought the Roman government closer to the renewed models of transnational security established in Counter-Revolutionary Europe.